2021
DOI: 10.1371/journal.pone.0245017
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification decreases grazing pressure but alters morphological structure in a dominant coastal seaweed

Abstract: Ocean acidification driven by anthropogenic climate change is causing a global decrease in pH, which is projected to be 0.4 units lower in coastal shallow waters by the year 2100. Previous studies have shown that seaweeds grown under such conditions may alter their growth and photosynthetic capacity. It is not clear how such alterations might impact interactions between seaweed and herbivores, e.g. through changes in feeding rates, nutritional value, or defense levels. Changes in seaweeds are particularly impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Susceptibility to grazing in F. vesiculosus and other fucoids can be affected by the morphology (e.g., toughness) and/or nutrient content (e.g., nitrogen content) of the thallus, as well as the presence of chemical defense compounds (e.g., phlorotannins). Changes in tissue toughness in F. vesiculosus were found by Rothäusler et al (2017) in response to reduced salinity and warming, as well as by Kinnby et al (2021) who found that seaweeds became more fragile under elevated pCO 2 . However, none of these previous studies found a correlation between tissue toughness and susceptibility to grazing (Rothäusler et al, 2017;Kinnby et al, 2021).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Susceptibility to grazing in F. vesiculosus and other fucoids can be affected by the morphology (e.g., toughness) and/or nutrient content (e.g., nitrogen content) of the thallus, as well as the presence of chemical defense compounds (e.g., phlorotannins). Changes in tissue toughness in F. vesiculosus were found by Rothäusler et al (2017) in response to reduced salinity and warming, as well as by Kinnby et al (2021) who found that seaweeds became more fragile under elevated pCO 2 . However, none of these previous studies found a correlation between tissue toughness and susceptibility to grazing (Rothäusler et al, 2017;Kinnby et al, 2021).…”
Section: Discussionmentioning
confidence: 77%
“…Changes in tissue toughness in F. vesiculosus were found by Rothäusler et al (2017) in response to reduced salinity and warming, as well as by Kinnby et al (2021) who found that seaweeds became more fragile under elevated pCO 2 . However, none of these previous studies found a correlation between tissue toughness and susceptibility to grazing (Rothäusler et al, 2017;Kinnby et al, 2021). Raddatz et al (2017) found a weak negative correlation between susceptibility to grazing and C:N ratio in F. vesiculosus, however, this was not related to changes in climate variables (pCO 2 or temperature).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations